Assessing the Efficacy of the Taxation System in Tanzania: Perspectives of Small and Medium Enterprises (SMEs) - Shafii Mshata; Nsubili Isaga (Universitas Airlangga, 2026)
Background: Small and Medium Enterprises (SMEs) are widely recognised as engines of economic growth, especially in developing countries such as Tanzania. Despite their economic importance, SMEs contribute only a small proportion of the tax base for a variety of reasons. While SMEs tax compliance has been widely studied, limited attention has been paid to post-reform perceptions and to how SMEs perceive tax fairness and administrative practices in low-trust environments. Objective: This study examines SMEs’ perceptions of the tax system’s effectiveness and identifies the challenges they encounter. Drawing on equity theory, this study contributes to the existing literature by examining how procedural, interactional, and distributive fairness shape taxpayers’ experiences. Method: Data were gathered from a survey of 239 owner-managers in Dar es Salaam, complemented with in-depth interviews. Quantitative data were analysed using descriptive statistics and t-tests, while qualitative data were thematically analysed to capture participants’ lived experiences. Results: SMEs perceive the tax system as inconvenient, incomprehensible, and uncertain. The study further revealed that perceptions of inequality and instability were not significant. Major compliance challenges identified include bureaucratic rigidity, lack of dialogue with tax authorities, and frustration with complex tax procedures. Conclusion: This study provides empirical insights into the post-reform context and extends equity theory conceptually to explain SMEs’ tax behaviour. The findings highlight the need for equity-informed and SME-responsive tax policies that simplify procedures, improve communication, and foster voluntary compliance. Keywords: Equity Theory; Revenue Mobilisation; SMEs; Tax Efficacy; Taxation System.